ANALISIS METAFORA DAN PERSONIFIKASI DALAM SYAIR PERANG SIAK KARYA DONALD J. GOUDIE - Sri Rahayu; Afrilia Ningtyas; Febby Febryanti; Hafara Nurisra; Ira Gustiana Sari; Nani Maulina; Tri Suci Handa Yani; Varira Candra Dewi (Kampus Akademik Publiser, 2026)
This study examines the use of figurative language, specifically metaphor and personification, in the Syair Perang Siak by Donald J. Goudie. The background of this research is based on the richness of classical Malay literature, which often conveys meaning indirectly through symbolic and imaginative language. The objective of this study is to identify, analyze, and interpret the forms and functions of metaphor and personification within the text. The research employs a descriptive qualitative method with a stylistic approach, focusing on the analysis of linguistic forms and their aesthetic and semantic functions. Data were collected through documentation techniques by selecting relevant lines containing figurative expressions. The findings reveal that metaphor is used to represent emotional conditions, shifts in power, and social realities through symbolic associations, while personification animates abstract concepts, creating a more vivid and dramatic narrative. Both figures of speech contribute significantly to enhancing the aesthetic quality and deepening the meaning of the text. The study implies that understanding figurative language in classical literature is essential to uncover cultural values, historical contexts, and the author’s perspective, as well as to enrich readers’ interpretative and analytical skills.